Transplant Recipients Using Tacrolimus Had Higher Utilization of Healthcare Services Than Those Receiving Cyclosporine in Taiwan - Lin, Yi-Chang; Tsai, Chien-Sung; Li, I-Hsun; Tsai, Yi-Ting; Huang, Tien-Yu; Lee, Kwai-Fong; Lin, Chih-Sheng; Shih, Jui-Hu; Kao, Li-Ting (Frontiers in Pharmacology, 2019)
To date, population-based study on the healthcare service utilization among stable heart, kidney, and liver transplant recipients with different calcineurin inhibitors is still scarce. Therefore, we used the Taiwan National Health Insurance Research Database to conduct a nationwide cross-sectional study to estimate the healthcare utilization of stable transplant recipients with tacrolimus or cyclosporine (n =3482). The sampled patients in this study comprised 377 heart, 1693 kidney, and 1412 liver transplant recipients between 1 January 2011 to 31 December 2011. Each subject was followed for a 1-year period to evaluate their healthcare service utilization. Outcome variables of the healthcare service utilization were stated as below: numbers of outpatient visits, outpatient costs, numbers of inpatient days, inpatients costs and total costs of all healthcare services. As for all healthcare service utilization, stable transplant recipients with tacrolimus had significantly more outpatient visits (40.7 vs. 38.6), outpatient costs (US$10,383 vs. US$8,155), and total costs (US$12,516 vs. US$10,372) of all healthcare services than those with cyclosporine during the 1-year follow-up period. Additionally, further analysis showed that heart transplant recipients receiving tacrolimus incurred 1.7-fold higher inpatient costs compared to patients receiving cyclosporine. We concluded that transplant recipients using tacrolimus had significantly higher utilization of all healthcare services than those receiving cyclosporine as immunosuppressive therapy.